Imaging and therapeutic applications of Zn(ii)-cryptolepine–curcumin molecular probes in cell apoptosis detection and photodynamic therapy. Issue 28 (10th March 2020) - Qin, Qi-Pin; Wei, Zu-Zhuang; Wang, Zhen-Feng; Huang, Xiao-Ling; Tan, Ming-Xiong; Zou, Hua-Hong; Liang, Hong
Abstract : The probes could synergistically promote mitochondrion-mediated apoptosis and enhance tumor therapeutic effects during photodynamic therapy. Abstract : Novel red Zn(ii ) complex-based fluorescent probes featuring cryptolepine–curcumin derivatives, namely, [Zn(BQ)Cl2 ] (BQ-Zn ) and [Zn(BQ)(Cur)]Cl (BQCur-Zn ), were developed for the simple and fluorescent label-free detection of apoptosis, an important biological process. The probes could synergistically promote mitochondrion-mediated apoptosis and enhance tumor therapeutic effects in vitro and vivo .